DEVELOPING GENDER CURRICULUM IN ISLAMIC HIGHER EDUCATION - Rosita Tandos (JURNAL SIPAKALEBBI, 2020)
Gender equality and justice are among the important topics to discuss not only at the practical level, but also in academic circumstances aiming to enlarge the framework and analysis of the issue. Integrating an Islamic perspective with other disciplines of study is a part of making it more applicable and down to the earth. Using a qualitative method and grounded theory approach, this study explored the point of developing a gender curriculum at Islamic Higher Education interconnected with an Islamic studies’ discussion. The participants of the study were lecturers and students from different faculties (Tarbiyah, Syariah, Ushuluddin, Adab, and Dakwah). The total participants were 50 people (n=50) consisting of 30 lecturers (n=30) and 20 students (n=20). They invited to complete a short list of close-ended questions and answer some open-ended questions covering points related to their knowledge, thoughts, and experiences, as well as topics related to designing a curriculum on gender and how to apply the gender issue. Three theoretical frameworks were used to analyze the topic and findings (Islamic perspective, gender curriculum, and community development theories). The community development approach was mainly used to explore principles and strategies that could be applied for community development to improve the implementation of the functions of Higher Education (conducting education, research, and community empowerment) and a strategic way to turn theories into practice.